The Impact Of Lumbar Stabilization Exercise On The Quality Of Life Of Pregnancy-Related Back Pain - Fatmarizka, Tiara; Nisa, Ivana Hanun; Mutiara, Farrah Rizky; Maghfiroh, Rinna Ainul (Universitas Muhammadiyah Surakarta, 2025)
Introduction: The developmental process of the fetus disrupts the daily activities of pregnant women, leading to musculoskeletal system disorders, mainly back pain. Fetal development causes postural changes and a shift in the body's centre of gravity to the anterior of the pregnant woman, resulting in paraspinal muscle tension and abdominal muscle weakness. Ignoring back discomfort during pregnancy can negatively affect a woman's overall health and happiness. Lumbar Stabilization Exercises are physical activities that aim to enhance neuromuscular function, strengthen the lower back, and improve flexibility, all of which contribute to maintaining spinal stability. This study aims to determine the effect of lumbar stabilisation exercise on the quality of life of pregnant women experiencing discomfort from back pain. Methods: The subjects of this study are pregnant women located at the Puskesmas Kartasura worksite who experience complaints of back pain. We assigned 11 respondents to the treatment group who underwent the exercise therapy known as LSE. We assigned another 11 respondents to the control group, who attended prenatal classes either in the village or at the clinic. We used the WHOQOOL Bref-Ina as the quality-of-life questionnaire. The data analysis involved using univariate analysis, normality tests, homogeneity tests, influence tests, and difference tests. Results: This study found that Lumbar Stabilization Exercise (LSE) affects the quality of life of pregnant women who report back pain (p = 0.000); however, there is no statistically significant difference (p = 0.902) between the treatment group and the control group. Conclusion: Lumbar Stabilization Exercises (LSE) effectively improve the quality of life for pregnant women experiencing back pain, as evidenced by significant improvements in physical, psychological, social, and environmental domains.